Bentuk Teknologi Modern yang Diciptakan di Masa Depan Dalam Novel Komet Karya Tere Liye - Grandis, Gayo Tectona; Arosyid, Muhammad Riduan; Kurniawan, Eva Dwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was conducted to show human activities in a parallel world in the novel Comet Tere Liye which tells of 3 characters who are looking for a comet clan which is surrounded by technology. The technology used is much more advanced and has very modern technological developments compared to human life in the earth clan. The main aim of this research is to explain several aspects of the technology being discussed which was created by humans in a parallel world and in the future this research will introduce technology similar to the Telecomet story to humans in the real world. able to provide inspiration for readers. The results of this research show that 1) The novel "Comet" by Tere Liye has values about technology through the depiction of activities carried out using modern tools. This type of research is descriptive and qualitative using the Miles and Huberman model design. The focus of this research is on the words, sentences and dialogue contained in the novel Comet by Tere Liye. In this research we found several findings that will be discussed, namely 1) capsules 2) holograms 3) translators 4) online transportation.